The multi-mode chaotic behaviors - Turk, Mustafa; Ata, Fikret (Emerald Group Publishing Limited, 2006)
Purpose - The purpose of this paper is to present a simulation and realization of the different types of chaotic attractors using the generalized Chua's circuit equations. Design/methodology/approach - This paper presents n + n-scroll and 2D n-scroll chaotic attractors by introducing multiple breakpoints to the nonlinearity. Two piece-wise linear elements controlled with x- and y-state space variables are used. Chaotic scrolls are originated through both x- and y-axes. The current feedback operational amplifiers are preferred in the experimental circuits because of their wide bandwidth. Findings - It is possible to increase the number of the scrolls in two directions by varying the number of breakpoints in the piece-wise linear characteristics or changing the location of equilibrium points of the system on 2D-plane. Theoretically developed behaviors are also experimentally tested. Originality/value - The excellent adaptation is observed between theoretical and experimental results. This paper also provides useful information about how to build the multiple breakpoints nonlinear elements using the simulation results.
Keywords: non-linear control systems; signal processing; simulation